STRATEGI PEMASARAN JASA PENDIDIKAN BERBASIS SEGMENTASI, TARGETING, POSITIONING, DAN DIFERENSIASI DI SD PLUS DARUL ULUM JOMBANG - Muhammad Rosyidi; Agus Irawan; Puput Sayidah Rahmaniyah; Sarman Fauziah (Jurnal Manajemen Pendidikan, 2026)
This study aims to comprehensively analyze the implementation of educational service marketing strategies through the Segmenting, Targeting, Positioning, and Differentiation (STPD) framework at Darul 'Ulum Jombang Elementary School Plus. The focus of this study is to evaluate the effectiveness of this strategic mix in increasing the interest of prospective parents during the New Student Admissions (PPDB) period amidst intense competition between institutions. Using a descriptive qualitative approach, primary data was obtained through in-depth interviews with school leaders as key informants. The research findings indicate that the school successfully integrated the STPD model dynamically by targeting the sociological needs of working parents and providing inclusive education services. The institution's position was strengthened through the synergy of the Islamic boarding school's spiritual values ​​with modern facilities, such as the full-day school system and the Al-Quran curriculum. Adaptive social media management and organic promotion proved effective in maintaining the stability of the enrollment quota. The novelty of this study lies in the adaptation model of Islamic educational institutions that is able to align traditional authority with contemporary managerial innovations, such as the implementation of cashless canteens. This strategy becomes a significant competitive advantage in areas with a high density of Islamic educational institutions